Identification of lncRNAs and Genes Responsible for Fatness and Fatty Acid Composition Traits between the Tibetan and Yorkshire Pigs - Peng Shang; Wenting Li; Gang Liu; Jian Zhang; Mengrou Li; Lvcao Wu; Kejun Wang; Yangzom Chamba (International Journal of Genomics)
Tibetan pigs from the Tibetan Plateau are characterized with a significant phenotypic difference relative to lowland pigs. In this study, a significant difference of the fatness and fatty acid composition traits was observed between the Tibetan and Yorkshire pigs. To uncover the involved mechanism, the expression profile of long noncoding RNAs (lncRNAs) and genes was compared between them. After serial filtered steps, 1,964 lncRNAs were obtained through our computational pipeline. In total, 63 and 715 lncRNAs and genes were identified to be differentially expressed. Evidence from cis- and trans-targeting analysis of lncRNAs demonstrated that some lncRNAs, such as MSTRG.14097 and MSTRG.8034, played important roles in the fatness and fatty acid composition traits. Bioinformatics analysis revealed that many candidate genes were responsible for the two traits. Of these, FASN, ACACA, SCD, ME3, PDHB, ACSS1, ACSS2, and ACLY were identified, which functioned in regulating the level of hexadecanoic acid, hexadecenoic acid, octadecenoic acid, and monounsaturated fatty acid. And LPGAT1, PDK4, ACAA1, and ADIPOQ were associated with the content of stearic acid, octadecadienoic acid, and polyunsaturated fatty acid. Candidate genes, which were responsible for fatness trait, consisted of FGF2, PLAG1, ADIPOQ, IRX3, MIF, IL-34, ADAM8, HMOX1, Vav1, and TLR8. In addition, association analysis also revealed that 34 and 57 genes significantly correlated to the fatness and fatty acid composition trait, respectively. Working out the mechanism caused by these lncRNAs and candidate genes is proven to be complicated but is invaluable to our understanding of fatness and fatty acid composition traits.